Case Report: Gastrointestinal neuroendocrine carcinoma with SMARCA4 deficiency: a clinicopathological report of two rare cases - Zhou, Ping; Fu, Yiyun; Wang, Weiya (Frontiers in Oncology, 2023)
Background: Gastrointestinal neuroendocrine carcinoma (GI NEC) is a rare but highly malignant neoplasm with an aggressive clinical course. SMARCA4 is one of the subunits of the SWI/SNF chromatin remodeling complex. SMARCA4 deficiency can occur rarely in subsets of NECs. Reports of the clinicopathological features of GI NECs with SMARCA4 deficiency are limited.In this study, we retrospectively reported two rare cases of GI NEC with SMARCA4 deficiency and described the clinicopathological, radiographic and histopathological features.Results: Case 1 was a 43-year-old male with a stage cT3NxM1, IV tumor. Case 2 was a 64year-old female with a stage cT4aN1M0, IIIA tumor. Both tumors presented as ulcerated masses with infiltration. Pathological examination indicated a solid architecture with poorly differentiated morphology, and complete loss of SMARCA4 (BRG1) was found.Immunohistochemical staining showed positivity for Syn, CgA and CD56. The Ki-67 index was 90% and 70%, respectively. None of the cases had mismatch repair deficiency (MMR).Case 1 received treatment with chemotherapy and anti-PD-1 immunotherapy. He did not respond to treatment, and died 9 months later. Case 2 received neoadjuvant chemotherapy before surgical treatment, and the tumor showed TRG3 in response to neoadjuvant chemotherapy, chemotherapy and anti-PD-1 immunotherapy were continued after surgical resection. There was no evidence of disease for 10 months.Conclusions: GI NEC with SMARCA4 deficiency is a rare entity of gastric NEC. SMARCA4 may be a promising targetable and prognostic biomarker. BRG1 immunohistochemical staining could be performed for GI NECs. Further studies with a larger cohort will be needed.